CONSTRUCTION OF A FINANCIAL PORTFOLIO ON THE BUCHAREST STOCK EXCHANGE USING RISK/RETURN ANALYSIS - MILOȘ, Laura Raisa; MILOȘ, Marius Cristian (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
The purpose of the paper is to present the advantages of the risk/return analysis when creating an optimum financial portfolio, with minimum risk, without sacrificing return. Having in consideration a holding period of three months (February-April 2014) and the stocks included in the Bucharest Stock Exchange index BET, we show how can be minimized the risk associated to the portfolio and which is the minimum variance point for a two titles portfolio.